METTL14-mediated m6A RNA methylation promotes the osteogenic differentiation of pPDLSCs by regulating WNT3A - Ma, Lan; Li, Min; Xuan, Guihong; Dai, Ying (Odontology, 2025)
Periodontitis is a chronic inflammatory disease that leads to the loss of periodontal supporting tissue. Furthermore, human periodontal ligament stem cells (hPDLSCs) are identified as candidate cells for the regeneration of periodontal and alveolar bone tissues. N6-Methyladenosine (m6A) performs a vital role in osteoporosis and bone metabolism. However, the role and mechanism of Methyltransferase-like 14 (METTL14) in the osteogenic differentiation of PDLSCs from periodontitis sufferers (pPDLSCs) is unclear. In this research, GSE223924 database analyzed the expression of METTL14 and Wnt Family Member 3A (WNT3A) in gingival tissue samples of 10 healthy subjects, 10 patients with periodontitis and peri-implantitis. RT-qPCR and western blot detected METTL14, COL1A1, Runx2, ALP, and WNT3A mRNA level and protein level. Osteogenic differentiation was evaluated by Alizarin Red S staining and ALP activity. MeRIP and dual-luciferase reporter assays verified interaction between METTL14 and WNT3A. GSE223924 database showed METTL14 was differentially expressed in patients with periodontitis and peri-implantitis. Furthermore, our data verified that METTL14 and WNT3A expression were decreased in pPDLSCs and were upregulated by osteogenic induction. METTL14 promoted osteogenic differentiation of pPDLSCs. METTL14 regulated WNT3A mRNA expression via m6A methylation. METTL14 facilitates osteogenic differentiation of pPDLSCs via modulating WNT3A, providing a possible target for improving alveolar bone regeneration outcomes.Highlights 1. METTL14 expression was decreased in pPDLSCs 2. METTL14 knockdown negatively regulated the osteogenic differentiation of pPDLSCs 3. WNT3A mRNA was a m6A-methylated target by METTL14.